The effects of isokinetic training in athletes after knee surgery: a systematic review - Petrucci, A.; Guglielmino, D.; Pecci, J.; Pareja-Galeano, H. (The Physician and Sportsmedicine, 2024)
Purpose To review the effectiveness of isokinetic training as an alternative method to traditional isotonic resistance training.